TYPES OF THE MASS MEDIA IN MODERN SOCIETY - Khamitov Eldorbek (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Given the increasing speed at which society is developing, the tightening of communication ties, the widespread adoption of Internet communication, and the fact that “of the most popular 10 million pages on the Internet, 54% are in English” [1], translating English-language texts in social networks presents its own unique challenges. The goal of this research is to catalogue the specifics of the Russian translation of contemporary English texts from mass media outlets, with a focus on social networks and news websites.